(untitled) (Contemporary Journal of Social Science Review, 2025)
In current education system Content and Language Integrated Learning (CLIL) is an efficient method of learning as well as critical skills. Due to the growing usage of English as EFL and ESL in schools in the bilingual education countries, the value of being able to teach English language by using the material from the other subject such as biology, history, computer, etc. The current paper provides an overview of four teachers’ perspectives on the implementation of CLIL at Community Model High School in Multan, Pakistan and highlights the efficacy of CLIL. The findings identified a number of success variables, including improved oral communication and cognitive abilities, enhanced multicultural awareness, and language development. However, study reveals some drawback of CLIL some teachers revealed that CLIL make learners confused as they are not attuned to study language and Biology simultaneously ad the restive role of administration in the implementation of CLIL at school level.